Tomatoes consumed in-season prevent oxidative stress in Fischer 344 rats: impact of geographical origin. Issue 18 (30th July 2021) - Cruz-Carrión, Álvaro; Ruiz de Azua, Ma. Josefina; Bravo, Francisca Isabel; Aragonès, Gerard; Muguerza, Begoña; Suárez, Manuel; Arola-Arnal, Anna
Abstract : In-season consumption of tomatoes improved or sustained antioxidant biomarkers, thus reducing oxidative stress values. The protective effect of tomatoes against oxidative stress depends on the geographical origin of the crop (LT or NLT). Abstract : Tomatoes ( Lycopersicon esculentum Mill.) constitute an important source of health-promoting compounds including bioactive antioxidants, such as flavonoids, that can differ in terms of composition and quantity depending on the conditions that tomatoes are cultivated. Otherwise, biological rhythms modulate oxidative stress. Therefore, the aim of this study was to evaluate the antioxidant properties of seasonally consumed tomatoes from two different geographical origins (local LT or non-local NLT) in Fischer 344 rats. The results show that LT and NLT have a specific phenolic signature and that each tomato gives a particular response toward biomarkers evaluated, which in turn showed a photoperiod-dependent effect. Remarkably, when tomatoes were administered in-season they improved or sustained antioxidant biomarkers, thus reducing oxidative stress values. It is noteworthy that the protective effect of tomatoes against oxidative stress depends on the geographical origin of the crop. Therefore, tomatoes consumed in-season may improve health by preventing oxidative stress.